Magnetic Materials: 2D‐Berry‐Curvature‐Driven Large Anomalous Hall Effect in Layered Topological Nodal‐Line MnAlGe (Adv. Mater. 21/2021). Issue 21 (26th May 2021) - Guin, Satya N.; Xu, Qiunan; Kumar, Nitesh; Kung, Hsiang‐Hsi; Dufresne, Sydney; Le, Congcong; Vir, Praveen; Michiardi, Matteo; Pedersen, Tor; Gorovikov, Sergey; Zhdanovich, Sergey; Manna, Kaustuv; et al.
Abstract : In article number 2006301, Satya N. Guin, Claudia Felser, and co‐workers report a layered topological nodal‐line magnet MnAlGe, which is composed of magnetic Mn square‐net layers that are separated by nonmagnetic Al–Ge spacers. The material exhibits a large anomalous Hall conductivity driven by the unique 2D Berry curvature distribution. From this work the search for new layered topological magnets and exploration of magnetism and topological properties are enabled.